Detection of SARS-CoV-2 in Different Types of Clinical Specimens - Wang, Wenling; Xu, Yanli; Gao, Ruqin; Lu, Roujian; Han, Kai; Wu, Guizhen; Tan, Wenjie (JAMA : the journal of the American Medical Association, 2020)
This study describes results of PCR and viral RNA testing for SARS-CoV-2 in bronchoalveolar fluid, sputum, feces, blood, and urine specimens from patients with COVID-19 infection in China to identify possible means of non-respiratory transmission.